SUN TZU’S STRATEGY FOR WINNING THE SUSTAINABLE TOURISM MARKET - Putra, Dyan Triana; Marhendi, Mengku; Mistriani, Nina; Susilaningtyas, Gesit; Setyaningtyas, Margaretha (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research examines the effectiveness of adopting Sun Tzu's strategies to achieve domination in the tourism business, resulting in the establishment of sustainable tourism. "The Art of War" is a classic Chinese work of strategy authored by philosopher Sun Tzu. It offers combat methods and highlights the importance of power in navigating a complex commercial environment. Entrepreneurs in any industry clearly recognise the need of maintaining higher levels of customer satisfaction for the sustainability of their business. The significant decrease in sales of business products can be attributed to the unsatisfactory levels of client satisfaction. Simultaneously, the persistent loss in sales numbers implies a significant risk of the business facing bankruptcy. Business managers must anticipate and strategize for competition from competitors, taking into consideration several factors. This research uses a qualitative research methodology. The findings demonstrate that the fundamental principles of Sun Tzu's Art of War can be effectively employed to attract customers in the tourism industry. This can be achieved by demonstrating respect towards customers, efficiently organising information, maintaining a clear focus on objectives, securing advantageous positions, launching strategic attacks, implementing unexpected tactics, skilfully manoeuvring, concentrating resources, leveraging economic power, establishing a resilient command structure, exhibiting strong leadership, and employing straightforward problem-solving techniques. Keywords: Sun Tzu Strategy; Tourism Market; Tourism Village; Sustainable Tourism